The next wave. (Economist, 2005)
The article discusses the growth of India's information technology (IT) and remote-service industries. Microsoft has announced plans to invest in India over the next four years, about half of it in adding to its existing research and development and technical-support operations. Investments by Microsoft and J.P. Morgan illustrate that a third stage of the great Indian services-export boom is well underway. In IT the growth in Indian exports is expected to come both from the software market, and from "traditional IT outsourcing"--such as remote management of whole systems, a market now dominated by the big global IT consultancies. India, with its English-language skills and common-law tradition is well-placed to secure a big share of the business. India's fundamental attraction has not changed since it first drew software developers: fantastic cost savings.